UPAYA MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA MELALUI PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD SISWA KELAS III SD NEGERI 142 PEKANBARU - Murni, Atma Murni Atma; Hutapea, Nahor Murani Hutapea Murani (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research is classroom action research. This research aims to increase the mathematics learning outcomes of students at class III SDN 142 Pekanbaru through the implentation of cooperative learning in the type Student Team Achiement Division (STAD). The subject of this research is 30 student at class III SD Negeri 142 Pekanbaru which consists of 16 boys and 14 girls with the heterogeneous ability level. This research consist of 2 cycles, of which each cycle in composed of stages, which is planning, implementation, observation, and reflection. The instrument of data collection in this research were observation sheet and the test mathematics learning outcomes. An action is deemed successful when the number of students that reached the Mastery Minimum Criteria had increased by the first and second daily exams. The qualitatif analysis descriptive narrative showed an improvement of learning process prior to the action of the first cycle to the second cycle. The result showed an increasing number of student who achieve the Mastery Minimum Criteria from the basic score with the percentage 59,17% to 66,9% on the first daily test and 74,13% on the second daily test. Based on that result, it can be concluded that the implentation of cooperative learning in the type Student Team Achiement Division (STAD) can improve the mathematics learning outcomes of students at class III SD Negeri 142 Pekanbaru on second semester academic years 2014/2015Key Words: The mathematics learning outcomes of students, Cooperative Learning in Type Student Team Achievement Division (STAD), Classroom action research.